MHE Testing in Real World Scenario - Lauridsen, Mette M. (J Clin Exp Hepatol, 2018)
Professional MHE awareness is high but when it comes to psychometric testing for MHE the real world scenario is characterized by hesitation and testing is offered only to selected cirrhosis patients. The hesitation is rooted in doubts about which tests to use, lack of knowledge about treatment benefits, and uncertainty about the tests’ ability to identify patients who will benefit from anti-HE treatment. Thus, the majority of MHE patients do not receive the available efficient anti-HE treatment. This mini-review attempts to quell some of these doubts.